Taktik MPR Angan Coffee and Comfort Food Dalam Meningkatkan Awareness - Yemima, Hana; Ayumi, Shereina Sarah; Sinuraya, Sofia; Perbawasari, Susie; Anisa, Renata (Marcommers : Jurnal Marketing Communication and Advertising, 2022)
Changing technology and increasing information encourages acceleration and lifestyle improvement. The growing lifestyle in the upper middle class that prioritizes drinking coffee as one of the activities they must do. To increase market demand for the need to drink coffee, Angan Coffee & Comfort Food also attended to answer the needs of the community. There are several coffee shops that are also present, for that Angan need Marketing Public Relations (MPR) to be able to compete and have certain characteristics that can distinguish Angan with other coffee shops. The purpose of this research is to describe the MPR activities conducted by Angan, as well as to analyse the success of the activities of MPR Angan. The MPR activities conducted by Angan is a form of workshop activities involving the public. So through this MPR activities can occur interaction between Angan and its target market, besides the event held by Angan is an activity that is an interest of the public itself. The research methods used in this research are qualitative descriptive research, which in this research, researchers becoming the key instrument. The technique of data collection used is an interview with the owner of the research subject, Angan Coffee and Comfort Food, and observe to visit Angan Coffee & Comfort Food. The result of a pull strategy with tactics derived in the form of events such as workshops, resulted in an increase in the attention of local communities around Jakarta to Angan Coffee and Comfort Food.